A Tourist Destination Planning and Design Model: Application to the Area around the Mi\~no River in the South of Galicia and the North of Portugal - Carmen Padin Fabeiro; Xulio Pardellas De Blas (European Regional Science Association (ERSA), 2003)
Based on a study of tourist activity as a factor influencing local development carried out in 2001 on Galicia and northern Portugal, our research team presents herein a synthesis of the main contributions offered by a territorial analysis of tourist destinations, drawing up a model which allows us to evaluate the characteristics of this border region. The main contribution of this study is the validation of the model used in order to propose planning measures, contrasting the initial hypothesis in regarding this region as a tourist destination as a whole, in terms of the structure of the features it has in common, analysed in the model, as well as the behaviour KEY WORDS: border region, destination regions, tourism planning
Keywords: 330